Major provisions of labour contracts and their theoretical coherence - Louis N. Christofides; Amy Chen Peng (Center for Economic Studies and ifo Institute (CESifo), 2006)
Theoretical work on indexation and contract duration suggests no role for the expected rate of inflation in equations explaining these variables. Yet, stand-alone or two-equation studies of indexation and contract duration often report that this variable is statistically significant. We study a wider econometric system which includes, in addition, non-contingent wage adjustment. This third, jointly dependent, variable and its nominal anchor (the expected rate of inflation) play a role in the duration and indexation decisions and offer a context within which earlier findings can be understood. In this three-equation system, the wage equation accommodates complex mechanisms through which price inflation feeds into wage adjustment both within and across contracts. The elasticity of indexation is modelled as a latent variable, supporting consideration of both the incidence and the intensity of indexation and linking consistently with the wage equation. In our results, the expected rate of inflation has no role in the duration equation and only a minor one in the elasticity of indexation equation. These findings are more consistent with received theory but they also suggest that more complex models involving all three variables and the sequence of contracts signed by a bargaining pair are needed.
Keywords: E31; J41; J50; 330